The predictive role of circulating microparticles in patients with chronic heart failure - Berezin, Alexander E.; Kremzer, Alexander A.; Martovitskaya, Yulia V.; Samura, Tatyana A.; Berezina, Tatyana A. (BBA clinical, 2015)
The study aim was to evaluate whether circulating microparticles with apoptotic or non-apoptotic phenotypes are useful for risk assessment of 3-year cumulative fatal and non-fatal cardiovascular events in CHF patients. The incidence of fatal and non-fatal cardiovascular events, as well as the frequency of occurrence of death from any cause in a cohort of 388 patients with CHF during 3 years of observation was studied prospectively. Circulating levels of NT-pro brain natriuretic peptide (NT-pro-BNP), high-sensitivity C-reactive protein (hs-CRP), and endothelial apoptotic microparticles (EMPs) were measured at baseline. Median follow-up was 2.32 years (IQR = 1.8-3.1). During follow-up, 110 cardiovascular events (including 43 fatal cases) were determined. Additionally, 74 subjects were hospitalized repetitively due to worsening CHF and also 16 subjects were readmitted in the hospital due to other cardiovascular reasons. In the univariate logistic regression analysis, the main factors independently related with cumulative endpoints were creatinine, fasting glucose, HbA1c, total cholesterol, uric acid, various types of EPMs, NT-pro-BNP, hs-CRP, NYHA class, decreased left ventricular ejection fraction (LVEF) less 45%, and type 2 diabetes mellitus. In multivariate model NYHA class, decreased LVEF (less 45%), NT-pro-BNP, hs-CRP, CD144 +/CD31 +/annexin V + EMPs, and CD31 +/annexin V + EMPs remained statistically significant for cumulative endpoint. Adding of CD144 +/CD31 +/annexin V + EMCs and CD31 +/annexin V + EMCs to the standard ABC model may improve the relative IDI for cumulative endpoint by 11.4% and 10.5% respectively. Apoptotic phenotype of circulating microparticles may relate 3-year combined clinical outcomes in CHF patients.